A Cubic El-Gamal Encryption Scheme Based On Lucas Sequence And Elliptic Curve - Tze Jin Wong; Lee Feng Koo; Fatin Hana Naning; Ahmad Fadly Nurullah Bin Rasedee; Mohamad Maulana Magiman; Mohammad Hasan Abdul Sathar (Union of researchers of Macedonia, 2024)
Non-Indexed Publication